2022
DOI: 10.1088/1748-0221/17/05/p05003
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a soft X-ray optimised CMOS Image Sensor

Abstract: A prototype CMOS Image Sensor optimised for soft X-ray applications has been designed by the Centre for Electronic Imaging in partnership with Teledyne-e2v. The device features four different pixel variants (three variants of 40 μm pitch pixels, and one variant of 10 μm pixels) each covering a quarter of the 2 × 2 cm2 image area. The pixel designs feature fully depleted pinned photodiodes using reverse substrate bias and have been optimised for low noise operation, high responsivity and low image lag. The fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This kind of detector belongs to the family of monolithic active pixels, developed primarily for imaging and high-density, high-resolution radiation detection applications. Being a sort of “camera on chip”, active pixel sensors integrate the electronic amplifier and have shown high potential and to be beneficial in the applications for high resolution imaging [ 23 , 24 , 25 ] and for radiation particle tracking [ 26 , 27 , 28 , 29 , 30 ]. An attempt to adopt such CMOS imaging devices for dosimetry has been proposed previously by [ 31 ] and also by [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…This kind of detector belongs to the family of monolithic active pixels, developed primarily for imaging and high-density, high-resolution radiation detection applications. Being a sort of “camera on chip”, active pixel sensors integrate the electronic amplifier and have shown high potential and to be beneficial in the applications for high resolution imaging [ 23 , 24 , 25 ] and for radiation particle tracking [ 26 , 27 , 28 , 29 , 30 ]. An attempt to adopt such CMOS imaging devices for dosimetry has been proposed previously by [ 31 ] and also by [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hull et al (2019) reported that 148 eV at 5.9 keV can be reached for a hybrid CMOS sensor, by applying pixel-bypixel gain correction. At around −30°C, Heymes et al (2022) reached a resolution of 142 eV at 5.9 keV with a CIS221-X sensor, and a backside illuminated version of this sensor reached 153 eV at 5.9 keV at −40°C (Stefanov et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, the performance of sCMOS sensors has been significantly improved, boasting faster readout speeds, superior irradiation resistance, and more flexible operating temperatures compared to traditional CCDs. Therefore, several X-ray space missions, such as Lobster Eye Imager for Astronomy (LEIA; Zhang et al 2022;Ling 2023), Einstein Probe (EP; Yuan et al 2018Yuan et al , 2022, and THESEUS (concept) (Heymes et al 2020(Heymes et al , 2022Stefanov et al 2022), used or will use sCMOS sensors as focal plane detectors.…”
Section: Introductionmentioning
confidence: 99%